If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 81 + 5y = -4y Solving 81 + 5y = -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 81 + 5y + 4y = -4y + 4y Combine like terms: 5y + 4y = 9y 81 + 9y = -4y + 4y Combine like terms: -4y + 4y = 0 81 + 9y = 0 Add '-81' to each side of the equation. 81 + -81 + 9y = 0 + -81 Combine like terms: 81 + -81 = 0 0 + 9y = 0 + -81 9y = 0 + -81 Combine like terms: 0 + -81 = -81 9y = -81 Divide each side by '9'. y = -9 Simplifying y = -9
| 2(6t+1)-4(t-1)= | | M^2-13m+26= | | 1/4-1/5= | | 10+9x=98-x | | 7+c=40 | | (c+4)(c-3)+6(1+c^2)=(c-2)(c+2) | | 213-4x=32x+21 | | 1/5(3x+12)=3(1-4x)+12 | | -x+4=5x+22 | | 2k+1=4 | | 6x+14=-51-7 | | c=0.10x+6 | | k(2.2)+k(1.8)+5=15 | | 12x=x/3 | | 6x+10=10x+2+5+1 | | 1/3(x+3)=1/6(2x+6) | | 6x+10=10x | | x+7/4=2x-7/4 | | 6x+7=3+8x-6 | | 22p-72=16-22p | | 11x-7x=-2 | | 3-6=2 | | x(3x)-5x=2 | | 5(y-3)=5-3y | | -(2x-1)=-5(2x+9) | | 1/8(x+8)=1/24(3x+24) | | 3x+5/4=4x-5/4 | | 3x-5(2x-1)=2(4x+7) | | g(2)=x^2-x | | 9x+27-6x+12=60 | | 6x+5=6x+21 | | -2x-10=6x+14 |